Music as Intangible Cultural Heritage Economic, Cultural and Social Identity - de-Miguel-Molina, Blanca; Santamarina-Campos, Virginia; de-Miguel-Molina, María; Boix-Doménech, Rafael (SpringerBriefs in Economics, 2021)
This open access book offers an interdisciplinary perspective and presents various case studies on music as ICH, highlighting the importance and functionality of music to stimulating social innovation and entrepreneurship. Intangible Cultural Heritage (ICH) covers the traditions or living expressions proposed by the 2003 Convention for the Safeguarding of the Intangible Cultural Heritage in five areas, including music. To understand the relationship between immaterial and material uses and inherent cultural landscapes, this open access book analyzes the symbolic, political, and economic dimensions of music. The authors highlight the continuity and current functionality of these artistic forms of expression as well as their lively and changing character in continuous transformation. Topics include the economic value and impact of music, strategies for social innovation in the music sector, music management, and public policies to promote cultural and creative industries.